Change and Transformation in Rural South India : Findings from Village Studies - G NIRANJAN RAO, K NARAYANAN NAIR (Economic and Political Weekly August 9, 2003, 2003)
A research project on village studies to analyse the facets of rural change and transformation in the southern states noted vastly different patterns of transformation in various states, and also that the pace and directions of change differed across villages, regions and states.